Proteomic analysis of extracellular matrix from the hepatic stellate cell line LX-2 identifies CYR61 and Wnt-5a as novel constituents of fibrotic liver - Rashid, S. Tamir (American Chemical Society, 2012)
[Image: see text] Activation of hepatic stellate cells (HSCs) and subsequent uncontrolled accumulation of altered extracellular matrix (ECM) underpin liver fibrosis, a wound healing response to chronic injury, which can lead to organ failure and death. We sought to catalogue the components of fibrotic liver ECM to obtain insights into disease etiology and aid identification of new biomarkers. Cell-derived ECM was isolated from the HSC line LX-2, an in vitro model of liver fibrosis, and compared to ECM from human foreskin fibroblasts (HFFs) as a control. Mass spectrometry analyses of cell-derived ECMs identified, with ≥99% confidence, 61 structural ECM or secreted proteins (48 and 31 proteins for LX-2 and HFF, respectively). Gene ontology enrichment analysis confirmed the enrichment of ECM proteins, and hierarchical clustering coupled with protein–protein interaction network analysis revealed a subset of proteins enriched to fibrotic ECM, highlighting the existence of cell type-specific ECM niches. Thirty-six proteins were enriched to LX-2 ECM as compared to HFF ECM, of which Wnt-5a and CYR61 were validated by immunohistochemistry in human and murine fibrotic liver tissue. Future studies will determine if these and other components may play a role in the etiology of hepatic fibrosis, serve as novel disease biomarkers, or open up new avenues for drug discovery.